2007
DOI: 10.1111/j.1574-695x.2007.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriflagella: antigenic profile and protective immunity

Abstract: Reproducible induction of sterilizing immunity, essential for an effective Helicobacter pylori vaccine, remains elusive. As motility is essential for gastric colonization by Helicobacter, we evaluated whether a vaccine targeting flagella induces improved protection. Mice immunized with a vaccine enriched for H. pylori flagella sheath proteins exhibited significantly reduced colonization, equivalent to that observed in mice immunized with whole-cell lysate. Two-dimensional profiles indicated that flagella conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…26 Additionally, whereas complete protection has been difficult to achieve in larger animal models, a subunit multivalent vaccine incorporating VacA, CagA, and Neutrophil Activating Protein (NAP) was shown to be protective when administered therapeutically in beagle dogs as measured by immunohistochemical detection of H. pylori in histologic sections. 27 Since a vaccine might require multiple antigens, it is encouraging that almost any H. pylori protein that has been tested so far seems to work as well as any other, including urease subunits, 28 CagA, 29 VacA, 29 catalase, 30 flagellin, 31 heat shock proteins, 26 H. pylori adhesion A, 32 NAP, 33 and others. Although whole cell lysate preparations have also been used extensively in mice as described in the initial Helicobacter vaccine reports, 34,35 the development of a human vaccine will require a better characterized, well defined product.…”
Section: Lessons From Small Animal Modelsmentioning
confidence: 99%
“…26 Additionally, whereas complete protection has been difficult to achieve in larger animal models, a subunit multivalent vaccine incorporating VacA, CagA, and Neutrophil Activating Protein (NAP) was shown to be protective when administered therapeutically in beagle dogs as measured by immunohistochemical detection of H. pylori in histologic sections. 27 Since a vaccine might require multiple antigens, it is encouraging that almost any H. pylori protein that has been tested so far seems to work as well as any other, including urease subunits, 28 CagA, 29 VacA, 29 catalase, 30 flagellin, 31 heat shock proteins, 26 H. pylori adhesion A, 32 NAP, 33 and others. Although whole cell lysate preparations have also been used extensively in mice as described in the initial Helicobacter vaccine reports, 34,35 the development of a human vaccine will require a better characterized, well defined product.…”
Section: Lessons From Small Animal Modelsmentioning
confidence: 99%
“…In addition, several laboratories have demonstrated that vaccine-induced protective immunity can be achieved in the absence of antibodies. [36][37][38] A partial list of antigens demonstrated to afford protection against H pylori in mice includes the urease subunits, 24 CagA, 23 VacA, 23 catalase, 39 flagellin, 40 heat shock proteins, 41 H pylori adhesion A, 42 and neutrophil activating protein (NAP). 43 Killed whole-cell bacteria may also suffice, as whole-cell lysates have been used extensively in mice as described in the original Helicobacter vaccine reports.…”
Section: Results From the Mouse Model That Contributed To Vaccine Devmentioning
confidence: 99%
“…Arguably the best option would be the production of a H. pylori vaccine, and several possible vaccine candidates are being researched [144146]. Vaccine components vary and include killed H. pylori whole cell extracts [147], heat shock proteins [148], flagellar antigens [144], adhesion antigens [149], lipopolysaccharide antigens [150], neutrophil activating protein [151], and urease [152].…”
Section: Alternative Treatments Methodsmentioning
confidence: 99%
“…Vaccine components vary and include killed H. pylori whole cell extracts [147], heat shock proteins [148], flagellar antigens [144], adhesion antigens [149], lipopolysaccharide antigens [150], neutrophil activating protein [151], and urease [152]. Unfortunately many of these are a long way from human trials [144146], and the inactivated whole cell extract were proven ineffective in a human volunteer study [153]. …”
Section: Alternative Treatments Methodsmentioning
confidence: 99%